2014
DOI: 10.1177/1049732314540054
|View full text |Cite
|
Sign up to set email alerts
|

What do Australian Women Experiencing Intimate Partner Abuse Want From Family and Friends?

Abstract: the magnitude of the problem, IPA is a major cause of death, disability, and illness among women aged between 15 and 44 years in Victoria, Australia (VicHealth, 2004; Vos et al., 2006). The problem has major societal costs in both social and economic terms; for example, in 2009 the annual cost of IPA in Australia was estimated to be 13.6 billion Australian dollars (Department of Families, Housing, Community Services and Indigenous Affairs, 2009). Given the prevalence and impact of IPA, the question of provisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 42 publications
0
16
0
3
Order By: Relevance
“…Literature from several studies from Western countries highlight the conditions under which women try to seek both formal and informal help to end IPV, and the factors they are associated with are women’s socio-economic status, ethnicity, culture, and religion (Taket et al, 2014). Although social norms have also been said to play a part, as IPV might be viewed as a private matter and seeking help comes with the loss of privacy (Liang et al, 2005), research has moved over the years to understand individual factors that may hinder help-seeking.…”
Section: Introductionmentioning
confidence: 99%
“…Literature from several studies from Western countries highlight the conditions under which women try to seek both formal and informal help to end IPV, and the factors they are associated with are women’s socio-economic status, ethnicity, culture, and religion (Taket et al, 2014). Although social norms have also been said to play a part, as IPV might be viewed as a private matter and seeking help comes with the loss of privacy (Liang et al, 2005), research has moved over the years to understand individual factors that may hinder help-seeking.…”
Section: Introductionmentioning
confidence: 99%
“…Disclosure of domestic violence has generally been found to be beneficial (Coker et al 2002) when the response is supportive and nonjudgemental (McCauley et al 1998, Spangaro et al 2009). However, some studies have found no benefit of disclosure (Ramsay et al 2002) and others reported detrimental impacts when responses to disclosure were negative (Goodkind et al 2003, Fanslow & Robinson 2010, Taket et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…3, awareness constrains the mobilisation of resources (both material and social), as a woman is unlikely to access available supports if she is not aware that they are needed. Building and maintaining support networks is also critical to mobilising for positive change, as friends and family can play an important role in helping a woman actually carry out the actions she has chosen [65] (e.g. providing a safe place to stay if she wishes to leave the perpetrator) and can help her feel that she is not alone.…”
Section: Discussionmentioning
confidence: 99%
“…with service providers) that are affirming. This needs to be followed up with validation in the form of feedback that is encouraging and supports a woman’s choices (whatever those choices may be) [65], and increases her understanding that she is heading down a pathway to healing. Throughout this process, the establishment and maintenance of trust is critical, and directly influences the level of comfort a woman will have in her interactions with others.…”
Section: Discussionmentioning
confidence: 99%